Kendali Mutu Produksi Concrete Tunnel Segment Berbasis Metode Six Sigma Proyek Pembangunan Mass Rapid Transit - Girsang, Hamonangan; Chamami , Ichsan (Universitas Kristen Maranatha, 2024)
Development infrastructure construction of MRT Jakarta Project Phase 2A with length is 5.8 kilometers consist of seven underground stations, production concrete tunnel segment done by XY company as the ability to meet the quality of Japanese Industrial Standard provides added value to the company. However during the production process concrete tunnel segment products often defects. This is in line with production report within 4 weeks which found defects. This study aims to determine the percentage of defects in the production of concrete tunnel segment and determine the factors causing occurrence of defects than improvements can be made to control production quality. The six sigma analysis method was used in this study by carrying out five stages of analysis are define, measure, analyze, improve, and control. This study result is average percentage of defects occurred is 5.80% with a total chipped defect of 54.21%, cracks 30%, chipped and cracks 15.26%, and rejects 0.53% with an average sigma level of 3.07. Factors are very decisive in controlling the production quality of the concrete tunnel segment are work methods, people management and tools, where are three factors a direct role during the production work process.